1997
DOI: 10.1177/112067219700700313
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Retinal Lesions and Axial Length, Age and Sex in High Myopia

Abstract: We analysed the relationship between central and peripheral retinal lesions and axial length (AL), patient's age and sex with myopia greater than 6 diopters. A total of 212 eyes of 109 patients with high myopia underwent detailed funduscopy and A-scan ultrasonography. AL was measured, and central and peripheral retinal lesions were noted. Results were analysed using Student's t-test. Sixty-one patients (118 eyes) were female and 48 (94 eyes) male. Mean age was 31.00 +/- 13.67 years, and mean AL was 28.31 +/- 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 14 publications
4
15
0
1
Order By: Relevance
“…As in the previous studies, the prevalence of myopic retinopathy in our study increased with the amount of myopia (Gözüm et al. ; Liu et al. ; Neelam et al.…”
Section: Discussionsupporting
confidence: 88%
“…As in the previous studies, the prevalence of myopic retinopathy in our study increased with the amount of myopia (Gözüm et al. ; Liu et al. ; Neelam et al.…”
Section: Discussionsupporting
confidence: 88%
“…Vongphanit et al. 12 examined 3585 participants and found the prevalence of myopic retinopathy increased with higher levels of myopia, from 1.0% of right eyes with myopia <−3.0 D to 52.4% of right eyes with myopia of at least −9.0 D. Earlier studies also showed a higher prevalence of pathological signs associated with greater axial lengths, 9,25 and many studies have shown that high myopia is generally axial in nature 26 . Several studies have demonstrated decreased ocular pulse and retinal blood flow with increasing myopia 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The associated lesions include a tessellated fundus, lacquer cracks, choroidal neovascularisation (CNV), and chorioretinal atrophy. Several risk factors for myopic maculopathy have been identified: axial length, posterior staphyloma, and the severity of myopia 8,9 . However, most large‐scale studies have been conducted in western countries and the Japanese population, 5,8–15 with limited assessment of risk factors for the different types and severity of high myopic maculopathy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As alterações na retina decorrentes de miopia maior que 6 D aumentam com o tamanho do globo e com a idade 31 . A progressão da miopia pode acarretar alterações oculares irreversíveis e perda da visão.…”
Section: Alterações De Fundo De Olhounclassified